Analysis of The Core Industry Determination of Cassava-Based Industrial Clusters Development in Jember Regency - Kurniawati, Emi; Subaktilah, Yani (Universitas Batanghari Jambi, 2024)
The cassava-based industry is an industry that processes cassava into various processed products. Development of cassava-based industry in Jember Regency can be carried out through a cluster approach. The cluster approach is a geographic concentration of interrelated and collaborating companies, involving suppliers of goods, service providers, core industries, related industries, and institutions. This research aims to determine the potential core industry of cassava-based industrial cluster development in Jember Regency. Analysis of the core industry of cassava-based industrial cluster development in Jember Regency was carried out using the AHP (Analytical Hierarchy Process) method. The research stages start from analysis, hierarchical structure, and AHP method to obtain core industry priorities. The research results show that the type of cassava-based industry that has the highest alternative weight is the tape industry with a weight of 0.415. The tape industry is the core industry with the most potential because in terms of 6 criteria, namely: the number of industries, market reach, production capacity, raw material potential, government policy, and access to investor funding, the tape industry has the highest weight. Based on this, the tape industry was chosen to be the core industry of cassava-based industrial cluster development in Jember Regency.